On the type of Schismotherium fractum Ameghino, 1887 (Xenarthra, Folivora, Megatherioidea) from the Early Miocene Santa Cruz Formation (Santa Cruz province, Argentina) - Racco, Augusto (2018)
Schismotherium fractum, the type species for the genus, is a basal Megatherioidea (Xenarthra, Folivora) from the Santa Cruz Formation (Early Miocene) of Patagonia. The type specimen, currently lost, was described as a fragmented left mandible. Several years later, Ameghino refined his description based on additional material that included the skull and mandible, and several postcranial elements, all deposited in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” (Buenos Aires, Argentina; MACN-A 6445-70). A neotype for this species is required to permit further systematic and taxonomic work on several sloth taxa, and we designate MACN-A 6445-70 as neotype for Schismotherium fractum.